Exploring the Interrelation between Traffic Congestion and Land uses in Amman: Challenges and Potential - Maram Tawil, Hamze Jawarneh (Journal for ReAttach Therapy and Developmental Diversities, 2023)
While traffic congestion is affecting life styles in cities and neighborhoods, this research paper is aiming at investigating and coming up with drivers that have and are causing traffic congestion in the different neighborhood of Amman. As a growing phenomenon in Amman, it was important to see where the roots for such are and try inevitably to conquer them and try to set up recommendations that can redirect planning regulations to proactively release the burden of such on residential neighborhoods. Two comparative case studies were adopted for this purpose, the residential neighborhoods Al-Baraka and Al-Hasaniyah, adjacent to main arterial streets Al-Madina Al-Munawwarah Street and Al-Hurriya Street.in Amman. The methods for this survey are on two levels, mixed methods using space syntax on one level, and interviews on the other level in addition to secondary and desk research analysis that contributed to building the bigger picture of what the case is in Amman. Findings have shown that the phenomenon of traffic congestion in the study area extends its roots in a complex way to include a variety of reasons such as the increasing rate of commercial land uses, population density, location in relation to the city, street penetration for residential neighborhoods, the inefficiency of the public transportation system and community culture. Such drivers were further synthesized to see in what ways certain adjacency and location can differ in impact than others.